Interactions with search systems - White, Ryen W. (Cambridge ; New York : Cambridge University Press, 2016)
"Search engines are an invaluable part of our daily lives. This book describes advances in technology, data availability, and searcher expectations around next-generation search engines. It will appeal to students (undergraduate/graduate) in disciplines such as Computer Science and Information Science, as well as scholars and scientists in related areas"--
Includes bibliographical references and index.
Keywords: Search engines -- Technological innovations; hakuohjelmat; systeemiajattelu; teknologinen kehitys; käyttäjälähtöisyys; tieto- ja viestintätekniikka; informaatiotutkimus